Circular economy, proximity, and shipbreaking: A material flow and environmental impact analysis. (20th June 2020) - Rahman, S.M. Mizanur; Kim, Junbeum
Abstract: Circular economy focuses on the extension of material and resource circularity within the economic system in order to minimize the extraction of natural resources. Attaining such circularity requires the integration of adverse impacts on the place in which the process takes place, as not all recycling activities occur within the same perimeter. The shipbreaking phenomenon epitomizes the circularity of metal that helps reaching the circular economy targets, but is often carried out far from the origin of the commodity, raising issues regarding proximate recycling. This study illustrates this aspect by analyzing the global ship flow pattern, domestic metabolism, and global environmental savings. Our results suggest that size of the ships rather than flagging pattern determines the recycling destination, as smaller ships are recycled in standard destinations despite being popularly flagged while large ships are recycled in substandard destinations despite being owned by standard recycling nations such as Turkey. We also see that shipbreaking avoids (70–90%) environmental impacts at the cost of (1–5%) disposal impacts and (5–20%) domestic processing impacts. Evaluating proximate recycling against distant recycling shows that the former performs worse by far (95 against 184) than the latter. We suggest that pursuing distant recycling rather than proximate recycling is globally imperative and thus, a beyond-border extended producer responsibility can be initiated to minimize beyond-border adverse impacts of distant recycling. Graphical abstract: Image 1